A comparative study on sample size requirements based on the methods of probits and logits. - Jardeleza, Ma. Theresa R.
An investigation in the area of sample size is pursued in this study and a comparative analysis between 2 methods, Probits and logits is likewise undertaken. Practical application of the formulas derived for sample size is used on data age at Menarche. The study design follows the dosequantal response scheme.